The psychological adaptation of the released prisoners in the Palestinian Preventive Security Service, Jenin Governorate, as a model - Shehadeh, Amer Saber Shehadeh; Jawabreh, Noor Mouyad Saleh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the methods of psychological and social adjustment from the point of view of the released prisoners and workers in the Palestinian Preventive Security Service in the Jenin Governorate. The researcher used a research tool prepared by researchers themselves, and the information was collected through the use of the descriptive analytical method for its relevance to this research. After conducting the interview, the two researchers analyzed the interviews according to thematic analysis method (Braun & Clarke, 2006). The researchers reached some of results, the most important of which are: that the prisoners talked about four main topics: (the suffering of the beginning of the arrest and its impact on the detainee, the suffering after the arrest process (inside the prison), support for the prisoners inside the prison and support for the captive after the liberation process, and each of the axes above was divided into several sub-themes according to the interview with ex detainees. The researchers came out with a set of recommendations, the most important of which is activating the role of centers and institutions concerned with the mental health of the released Palestinian detainees after being released from Israeli person, forming a professional team of psychologists specialized in the mechanism of dealing with the released prisoners, especially the problems they face upon leaving the captivity that hinder their adaptation, attention to the distribution of educational pamphlets It belongs to the released prisoners and activating the role of the media, locally and globally.